Nasal physiology and pathophysiology of nasal disorders - Onerci, T. Metin (Springer Berlin Heidelberg, 2013)
Nasal physiology and pathophysiology is a relatively neglected area, yet without a deep knowledge of the physiology it is impossible to understand the impact of structural changes and the process of disease development or to make sound treatment decisions. With the help of numerous tables, schematic drawings, and color photographs, this book will enable the reader to understand the nasal physiology and pathophysiology in detail. All four functions of the nose - respiration, defense, olfaction, and cosmesis  - are covered. Each chapter addresses one important aspect in an accessible way, and each is written by an acknowledged expert on the topic under consideration. The various techniques of clinical evaluation of nasal function are fully discussed, and current trends and future directions in nasal physiologic research are also explored. This book will be of value to both practicing otorhinolaryngologists and novices in the field.